Evaluating the phenomenological approach models in predicting the Neutron Induced Deuteron Emission Spectra from Different reactions - Hadi Jasim, Mahdi (Iraqi Journal of Science, 2023)
A neutron induced deuteron emission spectra and double differential cross-sections (DDX), in 27Al (n, D) 26Mg, 51V (n, D)50Ti , 54Fe ( n, D)53Mn and 63Cu (n, D) 62Ni reactions, have been investigated using the phenomenological approach model of Kalbach. The pre-equilibrium stage of the compound nucleus formation is considered the main pivot in the discription of cross-section, while the equilibrium (pick up or knock out ) process is analyzed in the framework of the statistical theory of cluster reactions, Feshbach, Kerman, and Koonin (FKK) model. To constrain the applicable parameterization as much as possible and to assess the predictive power of these models, the calculated results have been compared with the experimental data and other theoretical work such as TALYS code (Tendl-2014). The comparisons indicate good agreement between these models with the experimental data.